Glioblastoma Tumor Microenvironment and Purinergic Signaling: Implications for Novel Therapies - Martina Bedeschi; Elena Cavassi; Antonino Romeo; Anna Tesei (Pharmaceuticals)
Glial-origin brain tumors, particularly glioblastomas (GBMs), are known for their devastating prognosis and are characterized by rapid progression and fatal outcomes. Despite advances in surgical resection, complete removal of the tumor remains unattainable, with residual cells driving recurrence that is resistant to conventional therapies. The GBM tumor microenviroment (TME) significantly impacts tumor progression and treatment response. In this review, we explore the emerging role of purinergic signaling, especially the P2X7 receptor (P2X7R). Due to its unique characteristics, it plays a key role in tumor progression and offers a potential therapeutic strategy for GBM through TME modulation. We discuss also the emerging role of the P2X4 receptor (P2X4R) as a promising therapeutic target. Overall, targeting purinergic signaling offers a potential approach to overcoming current GBM treatment limitations.